Examining the role of high school athletic directors in promoting leadership development in high school student-athletes. Issue 1 (2nd January 2020) - Sturges, Alexander J.; Huysmans, Zenzi; Way, William; Goodson, Aaron
ABSTRACT: Leadership training is a valuable but underutilized process for high school student-athletes to experience. Athletic directors represent a unique opportunity to foster environments of leadership development in high schools. The purpose of the current study was to examine high school athletic directors' approaches to leadership development, and discuss the practical application of leadership programming. Interviews with nine athletic directors supported the value of sport as context for learning life skills, including leadership. Leadership development strategies included captain roundtables, provision of resources, and connecting networks of coaches. Differences existed across schools in leadership development prioritization and programming, indicating a lack of standardized programming between schools. The authors concluded that leadership is an essential component of high school athletics, and that it is pivotal to improve the delivery of leadership training through athletic directors. Further research on the topic is required to clarify best practice principles, and to evaluate athletic director programming.